Manufacture and Characterization of Physical Properties of Composites Based on Coconut Fiber Composition (Cocofiber) - Peggy Ananda Putri Adi Yunita; Nurfajriani (Universitas Lampung, 2025)
Manufacture and Characterization of Physical Properties of Composites Based on Coconut Fiber Composition (Cocofiber). This study aims to analyze the quality of coconut fiber reinforced composites through evaluation of physical properties including density, porosity, and water content. The composites were made using coconut fiber modified by immersion in 5% NaOH, epoxy resin as a matrix, and MEKPO catalyst using the hand lay-up method. Five variations of resin:fiber volume composition were used, namely 95:5%, 85:15%, 75:25%, 65:35%, and 55:45%. The results showed that the composite with 5% fiber content produced optimal performance with the highest density (0.94 g/cm³), the lowest porosity (22%), and the lowest water content (0.57%). Increasing fiber content tended to decrease density but increase porosity and water content, indicating that low fiber compositions resulted in better fiber-matrix bonding and potentially superior mechanical properties.